Effect of Small Sided Games Training Methods on Passing Accuracy in Athletes Balong Academy Football - Pipit Fitria Yulianto; Bagus Kuncor; Kodrad Budiyono; Aan Budi Santoso; Arif Rohman Hakim (Fair Play, 2024)
The aim of the research is to determine the effect of the small sided games training method on passing accuracy in football games among Balong Football Academy Karanganyar athletes in 2023.and if there is an influence then to find out how big it isThe influence of the small sided games training method on passing accuracy in football games among Balong Football Academy Karanganyar athletes in 2023. The research sample isAt Balong Football Academy Karanganyar Athletewith a total of 30 students. Sampling using techniquesporpusive sampling.The variable of this research is the resultPassing accuracywithsmall sided games practice as the independent variable and passing accuracy results as the dependent variable. The research design uses a pretest-posttest design.The test to determine passing accuracy uses the Passing accuracy testuse implementation instructionstest from (Dharmawan Effendy, 2015: 38).The research data analysis method usest-test formula calculated using a short formula. From the results of data analysis, conclusions are obtained: (1)There is an influence of small sided games training on the passing accuracy of football players among Balong Football Academy Karanganyar athletes in 2023 which is shown by the results of hypothesis testing with a paired sample t-test where the significance value is 0.000 < 0.05. (2) There was an increase in the passing accuracy of football players among Balong Football Academy Karanganyar athletes after the small sided games treatment as evidenced by the average pretest result of 8.60 and posttest result of 11.53, this shows an increase of 25.4%.